Historical aspects of formation of unqualification brazilians operary: market between work and school education - Silva, Hilda Maria Gonçalves da (Universidade Estadual de Campinas, UNICAMP, Unidade da Faculdade de Ciências Aplicadas de Limeira-SP, vinculada ao Laboratório de Estudos do Setor Público, LESP, 2011)
This study seeks to interpret the current context of the need to improve the quality of manpower in Brazil and its close relationship with the missing investment officer social policies geared towards the education of youths and adults. Thus, this work seeks to build a historical overview of adult education, which enables its integration with economic and social issues which have worsened or held back investment in education for youths and adults to broaden the expectation of social advancement of its target audience.